A study of the learning experience from an emerging technology integrated curriculum (International Journal of Scientific Research and Management (IJSRM), 2017)
This study aims to explore the learning effect of emerging technology integration in a senior high school curriculum as implemented by the High Scope Project of the Ministry of Science and Technology, R.O.C. Through senior high school teachers’ inquiry instruction and interaction with students, it explores students’ learning experience in an emerging technology integrated curriculum and further probes into subjects’ perception and effect of the experience. The research questions are: (1) What are the subjects’ past experience with emerging technology? (2) What is the subjects’ feedback from participating in an emerging technology integrated curriculum practiced by teachers? (3) What is students’ personal reflection after participating in an emerging technology integrated curriculum? This study adopts qualitative research of in-depth interviews, and the subjects are 6 students in one senior high school in southern Taiwan. Since the subjects are senior high school students who participate in an emerging technology integrated curriculum and the recorded interviews and observations are based on their agreement, this study practices purposive sampling. The research tool is the researcher’s self-designed interview outline. The study is based on multiple sources such as in-depth interviews, observations, and feedback. The main findings of this study are as follows: 1) senior high school students’ past behavior with emerging technology is rare; 2) teachers proposed practice courses that include immediate feedback and interaction, and these courses are the most popular with students. Teachers’ questions and encouragement and students’ problem-solving process result in students having a positive learning effect; 3) with experience from participating in competitions, students develop personal reflection and confidence. External praises lead to the construction of personal positive self-concept; 4) important self-reflection includes acquisition of new knowledge, passion in attempts, demand for a great amount of originality and ideas, etc.